Peran Tim Kesehatan Gigi dalam Penanganan Kesehatan Gigi dan Mulut - Hazmia Arsil; Farisza Gita Roemoso; M. Nasrul; Tri Budi W. Rahardjo (Faculty of Dentistry, Universitas Indonesia, 2015)
Routine oral health care, have never been considered as an important procedure of duty care at the geriatric ward earlier. Poor oral codition were commonly found in geriatric patients, especially those wearing dentures. This condition usually occur due to the general condition of the patient that is weak or immobilized. Therefore geriatric ward nurses should be able to maintain the oral health as well as the patients dentures and to idenfify any oral lesion, also that related to dentures and referral system. A good teamwork among physician, dentist, and nurses in a health team for geriatric patients will improve the patients' oral health care which will support their general health accordingly.